2023
DOI: 10.1093/forestry/cpad002
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground responses to belowground root damage detected by non-destructive sensing metrics in three tree species

Abstract: Root systems form a significant part of tree biomass and function. Yet, roots are hidden from our eyes, making it difficult to track the belowground processes. By contrast, our capacity to detect aboveground changes in trees has been continuously improving using optical methods. Here, we tested two fundamental questions: (1) To what extent can we detect aboveground responses to mechanical damage of the root system? (2) To what extent are roots redundant? We applied three different non-destructive remote sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Carob also has an extensive root system that penetrates deep into the soil-similar to Pistacia lentiscus-with the ability to develop new, deep roots at times of low water moisture content (Christodoulakis, 1992), thus funding the water loss caused by open stomata. Lateral roots formed c. 50% of root biomass of 2.3-year-old seedlings, similar to that in Quercus coccifera and Pinus halepensis (Azar et al, 2023). The roots of experimentally unwatered plants were found to be shorter than those of well-watered plants, but root dry mass of unwatered plants in the upper soil horizons was similar to that of well-watered plants.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Carob also has an extensive root system that penetrates deep into the soil-similar to Pistacia lentiscus-with the ability to develop new, deep roots at times of low water moisture content (Christodoulakis, 1992), thus funding the water loss caused by open stomata. Lateral roots formed c. 50% of root biomass of 2.3-year-old seedlings, similar to that in Quercus coccifera and Pinus halepensis (Azar et al, 2023). The roots of experimentally unwatered plants were found to be shorter than those of well-watered plants, but root dry mass of unwatered plants in the upper soil horizons was similar to that of well-watered plants.…”
supporting
confidence: 63%
“…The primary roots also have large stomata that are permanently open which may increase gas exchange or increase water and nutrient uptake (Christodoulakis et al, 2002). The importance of the roots in water supply in carob was demonstrated by Azar et al (2023) who showed that carob shoots were more highly stressed by experimental root loss of up to 75% of their depth than either Pinus halepensis or Quercus coccifera.…”
mentioning
confidence: 99%
“…NDWI values vary between -1 and +1 depending on the leaf water content, vegetation type, and cover. Although some other variations of this index exist (e.g., Azar et al, 2023;Helman and Mussery, 2020), this version is most robust for detecting vegetation water content because of its use of the reflectance at the SWIR bands in Eq. 3, which is known to be sensitive to changes in mesophyll water content (Ceccato et al, 2001;Tucker, 1980).…”
Section: Ndwimentioning
confidence: 99%
“…NDWI values vary between −1 and +1 depending on the leaf water content, vegetation type, and cover. Although some other variations of this index exist (e.g., Azar et al., 2023; Helman & Mussery, 2020), this version is most robust for detecting vegetation water content because of its use of the reflectance at the SWIR bands in Equation , which is known to be sensitive to changes in mesophyll water content (Ceccato et al., 2001; Tucker, 1980). Since the water use of the vegetation in hyperarid regions is typically low, we expect NDWI to be highly sensitive to new water supply by floods.…”
Section: Data Sourcesmentioning
confidence: 99%